THE MODERATING EFFECTS OF ENTREPRENEURIAL EDUCATION AND EXPERIENCE ON THE RELATIONSHIP BETWEEN CAPITAL WITH SMALL AND MEDIUM ENTERPRISES PERFORMANCE - Nelly Astuti (Universitas muhammadiyah malang, 2021)
This paper examines the moderating effect of entrepreneurial education and experience on the relationship between capital and Small and Medium Enterprises (SMEs) performance. The reason is that the relationship has been tested by researchers, but the results are inconsistent. For that purpose, 6 SMEs and their entrepreneurs were randomly selected to be the objects and subjects in this study. The data analysis used a linear regression model, and the results showed: (1) Capital is positively and significantly related to performance, but the performance of SMEs which are controlled by male entrepreneurs is superior to that of female entrepreneurs; (2) education and experience of entrepreneurs significantly strengthen the relationship between capital and performance. However, the full moderation effect is stronger than the partial moderation effect. This means that education and experience moderate the relationship together, and not separately. From the gender perspective, the moderation effect was also superior for SMEs controlled by male entrepreneurs than for female entrepreneurs.